The Relationship between Customer Value and Customer Satisfaction in Face-to-face Tutorials at Universitas Terbuka - Herman (AAOU Journal, 2014)
This article discusses the relationship between Customer Value and Customer Satisfaction in the context of face-to-face tutorials at Universitas Terbuka, Indonesia. In this study, the idea — which was derived from marketing theory for tangible products — was implemented for face-to-face tutorial services. The sample consisted of 200 students involved in face-to-face tutorials whose perceptionsof the tutors' performance, tutorial results, tutorial costs and students' satisfactionwere measured by using six scales.Customer Value consists of the tutors' performance, tutorial results and tutorial costs; and Customer Satisfaction was derived from SERVQUAL. The findings show that there is a significant positive correlation between Customer Value and Customer Satisfaction. This finding indicates that marketing theory for tangible product can also be used for face-to-face tutorials as an intangible product.